Studi Kasus Amsal Christy Sitepu: Analisis Disparitas Pertimbangan Hakim dalam Perkara Tindak Pidana Korupsi Berbasis Jasa Kreatif - CITA MALIKA PRAHASTI HANDOKO (Jurist Argumentum: Pemikiran Intelektual Hukum, 2026)
This study examines judicial disparity in the corruption case of Amsal Christy Sitepu by focusing on a creative-service-based dispute, namely the production of village profile videos. The case is academically significant because the object of the dispute is not a conventional physical procurement project, but an intangible creative service whose economic value is determined by ideas, technical work, and audiovisual production processes. The study aims to identify the pattern of judicial considerations, assess the existence of disparity between aggravating and mitigating considerations, and explain how the character of creative services influences judicial criminal assessment. Using a normative legal method with a juridical-normative approach, this research relies on library research and document analysis of primary, secondary, and tertiary legal materials. The analysis is conducted descriptively and interpretatively, with frequency-and-weight scoring used only as an auxiliary tool to observe judicial tendencies. The findings indicate that the core dispute lies not in the absence of work, but in the valuation of creative components such as concept development, editing, cutting, dubbing, and microphone use, which were disputed by the prosecutor and auditor as zero-valued items. At the same time, the evidentiary record shows that the work was completed, delivered, and regarded as beneficial by village heads, while the panel of judges ultimately concluded that the element of unlawful conduct was not proven and acquitted the defendant.  The case demonstrates that the intangible character of creative services complicates the construction of state-loss evidence and can shift judicial attention from a purely numerical assessment toward a more contextual evaluation of professional judgment, contractual performance, and criminal liability. Accordingly, the study argues that judicial disparity in corruption cases may arise not only from differences in weighing aggravating and mitigating factors, but also from the evidentiary instability created by creative-service valuation.